Allometric analysis of the ontogenetic variation and evolution of the skull in Caiman spix, 1825 (Crocodylia: Alligatoridae) - Monteiro, Leandro R. [UNESP] (1997)
We studied ontogenetic variation in the shape of the skull among species of Caiman using principal component analysis. Comparison of multivariate allometric coefficients and ontogenetic trends between size and shape reveals that C. sclerops and C. yacare have similar ontogenetic processes, and they are more related to each other than either is to C. latirostris. Allometric relationships of the characters measured are similar in all species studied. The greater differences were in the width measurements, with higher coefficients in shape (second principal component) for C. latirostris, and length measurements with higher coefficients in shape for C. yacare and C. sclerops. The ontogenetic process leading to change in skull shape in the group seems to be plesiomorphic for elongation and derived for broadening. Statistical comparison of the ontogenetic trends with models of allometric heterochrony suggests that C. latirostris has diverged from the other species by a neotenic process, and that C. sclerops is separated from C yacare by ontogenetic scaling (progenesis).